Medieval Christian Dualist Perceptions and Conceptions of Biblical Paradise - Stoyanov, Yuri (Studia Ceranea, 2013)
The article intends to draw attention to some of the most significant and telling appropriations of traditional themes of Biblical paradise in medieval Christian dualism (namely, Paulicianism, Bogomilism and related groups in Eastern Christendom and Catharism in Western Christendom) and initiate discussion on the important but presently not always explicable problem of their theological and literary provenance. The significance of this problematic is highlighted by the increasing amount of direct and indirect evidence of the role played by a number of early Jewish and Christian pseudepigraphic works in the formation of medieval Christian dualist cosmogonic, cosmological, satanological, Christological and biblical history traditions. The preliminary survey of medieval dualist conceptions of biblical Paradise shows also once more that the doctrinal evidence for Bogomilism and Catharism is too complex and polyvalent to be defined or ignored apriori as representing medieval heresiological constructs drawing on earlier heresiological texts and stereotypes. The material examined in the article shows that the text-critical treatment of the primary sources to first establish the most plausible literary and theological provenance of the respective teachings attributed to medieval Christian dualist groups or individuals still remains indispensable to the study of medieval heresy and needs to precede the application of models and approaches drawn from contemporary anthropological and sociological theory to the source material.